The interface between intellectual property and investment law : an intertextual analysis - Oke, Emmanuel Kolawole (Elgar intellectual property and global development series, 2021)
"This original book presents a critical analysis of the interface between international intellectual property law and international investment law through the lens of intertextuality. It argues that a structuralist approach to intertextuality can be useful in the context of legal interpretation, especially in relation to the interpretation of treaties. Emmanuel Kolawole Oke critically evaluates the assumption that investment tribunals cannot take the rules of international intellectual property law into account when resolving investment disputes concerning intellectual property rights. He demonstrates instead the ways in which investment tribunals can and should adopt an intertextual approach when resolving such disputes, which, in turn, will help to preserve the intellectual property policy space of host states. Providing useful and thought-provoking insights, this book will be beneficial for legal scholars and students in the fields of intellectual property law, international investment law, and human rights. It will also be of great assistance to arbitrators faced with investment disputes involving intellectual property rights, as well as policy makers engaged in the negotiation of trade and investment agreements"--